Operational Research / Analysis and Applications - Wilkes Michael (Mcgraw Hill Book Company, 1989)
A new introductory text for undergraduates in business studies, management, accounting and economics. The text adopts a modular approach to operational research and most chapters are largely self-contained. Preface, Introduction, Linear Programming - Introduction and Graphical Method, Linear Programming - The Simplex Method, Transportation Problems, Assignment Problems, Investment Appraisal, Critical Path Method, Stock Control, Queueing Theory, Expected Values and Decision Trees and Break-even Analysis, Statistical Replacement Methods, Forecasting Methods, Simulation, The Theory of Games, Sequencing Problems, Dynamic Programming, Appendix: Tables, Index.